Penerapan Teknik Tari Tradisi Minangkabau Untuk Meningkatkan Kemampuan Menari Tari Piriang Syofyani dalam Kegiatan Ekstrakurikuler di SMAN 1 Ampek Angkek - Trilesia Putri; Esy Maestro (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
This study aims to describe the application of Minangkabau dance techniques to improve the ability to dance the Creative Piring Dance of SMA N 1 Ampek students. This type of research is qualitative research with a descriptive method. Data was collected through literature studies, observations, interviews, documentation. The data in this study uses primary data and secondary data. The steps of analyzing data are the process of data collection, data reduction, data presentation and conclusion drawn. The results of the study show that the methods used in the extracurricular art of piriang dance created by Syofyani are lectures, demonstrations and practice methods. While the infrastructure facilities are still in an inadequate condition even though in general they have been implemented well, the infrastructure facilities in this activity include mobile phones and Spekear. The assessment of the implementation of extracurricular activities in dance at SMAN 1 Ampek Angkek is a direct assessment, namely during the training process, disciplinary assessments are directly given qualitatively such as: A (Very Good) which is given with a score range of 85-100, B (Good) which is given a range of 76-84, C (Adequate) which is given a range of 65-75, D (Less) which is given a range of 55-64. It can be concluded with the implementation of extracurricular piriang dance art created by Syofyani at SMAN 1 Ampek Angkek by applying discipline, continuous practice, being given facilities to develop the quality of skills, talents and interests of students as well as training confidence and ability in dance.